TRANSFORMASI STRATEGI KOMUNIKASI PENERIMAAN MAHASISWA BARU DI PTKIN UNTUK MENARIK MINAT GEN Z - Hadi, Abdul; Apriko, Muhammad Syendi (Linimasa : Jurnal Ilmu Komunikasi, 2026)
This study examines the transformation of new student admission strategies at State Islamic Religious Universities (PTKIN), with a focus on UIN Raden Fatah Palembang, in responding to the dynamics of Generation Z interest as the dominant demographic group of prospective students. Generation Z is characterized by dependence on digital information, a preference for interactive and flexible learning environments, and a strong orientation toward values and identity. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, observations, and document analysis involving university leaders, admissions staff, faculty representatives, and Generation Z students. Thematic analysis produced five main findings: (1) a transformation from a conventional bureaucratic model toward a technology-based adaptive system, such as SSE UMPTKIN and multiple selection pathways (SPAN-PTKIN, UMPTKIN); (2) Generation Z’s preference for digital engagement, authenticity, and career relevance; (3) the intensive use of digital tools, including Instagram, TikTok, webinars, and virtual campus tours as effective recruitment media; (4) efforts to balance Islamic identity with modern digital strategies; and (5) increased institutional competitiveness through strengthened branding and promotional reach. This study concludes that PTKIN’s transformation strategy strongly resonates with Generation Z through the integration of technological innovation and cultural authenticity. Social media campaigns and career-oriented messaging not only enhance prospective student engagement but also strengthen institutional credibility and differentiation. These findings contribute to broader discussions on educational transformation in Indonesia by highlighting how Islamic higher education institutions navigate the tension between tradition and innovation to remain sustainable and competitive.